Studi Teoritis Metode Pendidikan Islam Berdasarkan Konsep Al Thoumy Al Saibany - Afif, Nur; Zaini; Alam, Mufassirul (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
This research aims to examine Islamic education methods based on philosophical concepts and the application of the Al Thoumy Al Saibany Concept in Islamic Education. The research approach uses a qualitative approach and literature review methods. This research is based on library methods, namely references, theoretical studies, scientific literature, and other references. The results of this research explain that 1) Islamic education methods are based on philosophical studies. Education as a very strategic and potential institution in developing and fostering moral behavior, which should be directed at developing humanity; 2) critical and innovative thinking as expressed by Al Syaibani, in the context of advancing the world of Islamic education. Al-Syaibani's concept states that the highest goal of Islamic education is to prepare for life in this world and the afterlife.